Evidence for Ancestral Programming of Resilience in a Two-Hit Stress Model - Faraji, Jamshid; Soltanpour, Nabiollah; Ambeskovic, Mirela; Zucchi, Fabiola C. R.; Beaumier, Pierre; Kovalchuk, Igor; Metz, Gerlinde A. S. (Frontiers in Behavioral Neuroscience, 2017)
In a continuously stressful environment, the effects of recurrent prenatal stress (PS) may accumulate across generations and alter stress vulnerability and resilience. Here, we report in female rats that a family history of recurrent ancestral PS facilitates certain aspects of movement performance, and that these benefits are abolished by the experience of a second hit, induced by a silent ischemia during adulthood. Female F4-generation rats with and without a family history of cumulative multigenerational PS (MPS) were tested for skilled motor behaviours before and after the induction of a minor ischemic insult by endothelin-1 infusion into the primary motor cortex. MPS resulted in improved skilled motor abilities and blunted hypothalamic-pituitary-adrenal (HPA) axis function compared to non-stressed rats. Deep sequencing revealed downregulation of miR-708 in MPS rats along with upregulation of its predicted target genes Mapk10 and Rasd2. Through miR-708 stress may regulate MAPK pathway activity. Hair trace elemental analysis revealed an increased Na/K ratio, which suggests a chronic shift in adrenal gland function. The ischemic lesion activated the HPA axis in MPS rats only; the lesion, however, abolished the advantage of MPS in skilled reaching. The findings indicate that MPS generates adaptive flexibility in movement, which is challenged by a second stressor, such as a neuropathological condition. Thus, a second ‘hit’ by a stressor may limit behavioural flexibility and neural plasticity associated with ancestral stress.